Structure and histology of extrafloral nectaries of tropical species in a mexican rain forest - Rodríguez-Morales, Dulce (2016)
Although there is a large diversity of plant species with extrafloral nectaries, histological detail of these glands is poorly documented in tropical rain forest species. We characterized extrafloral nectaries using digital photographs, scanning electron microscopy and histological methods for eight plant species belonging to the Costaceae, Euphorbiaceae, Malvaceae and Salicaceae. To our knowledge, there are no previous reports on the structure of extrafloral nectaries for these species. Croton species exhibited reddish extrafloral nectaries on the petioles, surrounded by star-shaped trichomes. Cnidoscolus multilobus and Omphalea oleifera showed green, elevated, extrafloral nectaries at the peduncle; C. multilobus showed abundant secretory tissue; O. oleifera revealed numerous cells with calcium oxalate crystals. Heliocarpus species showed extrafloral nectaries distributed at the base of the blade and possesses glands in the center of the extrafloral nectary surrounded by a series of parenchymatic cells. Pleuranthodendron lindenii has two extrafloral nectaries at the base of the leaves. Costus scaber has a hollow-type extrafloral nectary on the red-colored bracts of the inflorescence; nectar cavity is found in the center area of each bracts located on a yellow line. The extrafloral nectaries described in this study exhibited different morphologies and histological structures involved in the secretion of extrafloral nectar that could be related to biotic defenses, primarily by attracting ants.